NGTS-21b: an inflated Super-Jupiter orbiting a metal-poor K dwarf. Issue 3 (7th October 2022) - Alves, Douglas R; Jenkins, James S; Vines, Jose I; Nielsen, Louise D; Gill, Samuel; Acton, Jack S; Anderson, D R; Bayliss, Daniel; Bouchy, François; Breytenbach, Hannes; Bryant, Edward M; Burleigh, Matthew R; et al.
ABSTRACT: We report the discovery of NGTS-21b , a massive hot Jupiter orbiting a low-mass star as part of the Next Generation Transit Survey (NGTS). The planet has a mass and radius of 2.36 ± 0.21 M J and 1.33 ± 0.03 R J, and an orbital period of 1.543 d. The host is a K3V ( T eff = 4660 ± 41 K) metal-poor ([Fe/H] = −0.26 ± 0.07 dex) dwarf star with a mass and radius of 0.72 ± 0.04 M⊙ and 0.86 ± 0.04 R ⊙ . Its age and rotation period of 10.02^+3.29_-7.30 Gyr and 17.88 ± 0.08 d, respectively, are in accordance with the observed moderately low-stellar activity level. When comparing NGTS-21b with currently known transiting hot Jupiters with similar equilibrium temperatures, it is found to have one of the largest measured radii despite its large mass. Inflation-free planetary structure models suggest the planet's atmosphere is inflated by \! 21 per cent, while inflationary models predict a radius consistent with observations, thus pointing to stellar irradiation as the probable origin of NGTS-21b's radius inflation. Additionally, NGTS-21b's bulk density (1.25 ± 0.15 g cm –3 ) is also amongst the largest within the population of metal-poor giant hosts ([Fe/H] < 0.0), helping to reveal a falling upper boundary in metallicity–planet density parameter space that is in concordance with core accretion formation models. The discovery of rare planetary systems such as NGTS-21 greatly contributes towards better constraints being placed on the formation and evolution mechanisms of massive planets orbiting low-mass stars.